PARAMETERS OF VIBRATION IMAGING AND PSYCHOPHYSIOLOGICAL REACTIONS IN HIGHLY QUALIFIED ATHLETES SPECIALIZING IN BULLET AND BENCH SHOOTING - Sturchak, I.S.; Abramova, T.F.; Nikitina, T.M.; Polfuntikova, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the information content of the innovative vibraimage technology (VibraMed10, 2020), taking into account the psychophysiological indicators of the state of athletes. Methods and structure of the study. In the course of scientific work, methods of vibraimaging and psychophysiological testing were used to analyze the current state of 58 highly qualified athletes specializing in bullet and clay shooting. A statistical analysis of the parameters of the vibraimage and psychophysiological reactions was carried out. The informative significance of the indicators determined when using the technology of vibraimage to assess the psychophysiological state of highly qualified athletes specializing in bullet and bench shooting has been determined. Results and conclusions. The conducted pilot study indicates the possibility of using the technology VibraMed10 to monitor the psychophysiological state of athletes in the process of training and competitive activities. This is confirmed by the identification of common characteristics, such as "self-regulation", "energy", "charisma", "aggressiveness", "stress", "anxiety", "depression" and "danger", which are typical for shooting sports athletes in general. Along with this, differences were found in the severity of the parameters: "poise", "neuroticism" and "inhibition", which can be attributed to the priority signs of belonging to a narrow specialization.